Examining The Risk Of Brain Drain And Lower Remittances - Mendoza, Ronald U (Archīum Ateneo, 2013)
Developing countries could be facing two linked trends that are potentially detrimental to their development prospects: outmigration of high-skilled professionals and the potential decline in remittances as migrants with higher skills may be less likely to remit or may remit less if they do. This paper examines this policy issue by empirically analyzing a cross-national dataset spanning 70 countries during the period 1985–2000, as well as a country-specific dataset for the Philippines. It finds little evidence that high-skilled migration is linked to lower remittances at the aggregate level. This finding coheres with more recent studies leveraging microlevel data.